Design High-Q Square Resonator Add-Drop Filter for CWDM Application - Abdul Latiff, Anas; Abdul Rahim, Hazli Rafis; Jaafar, Anuar; Gannapathy, Vigneswara Rao; Zainuddin, Muhammad Noorazlan Shah (AJBAS, 2013)
The high-Q square resonator as an add-drop filter is proposed and demonstrated using commercially available two-dimension (2D) of finite-difference time-domain (FDTD) method. Simulation is on a high-index contrast laterally waveguide-coupled square resonator in the 1.55 μm wavelength grid and the air-gap size fixed to 0.18 μm. Widths of the waveguide-coupled and diameter of square micro cavities are varied from 0.22 - 0.37 μm and 3.6 - 6.0 μm, respectively. The pulse excitation signal with fundamental slab mode is launched into the planar waveguide-coupled. Time monitor implement the fast Fourier transform analysis. RSoft software is used to simulate this filter. The add-drop filter has been successfully designed and analyzed with wide free-spectral range (FSR) of 28 nm, higher quality factor (Q) than 1000 and extinction ratio (ER) of 3.9 dB. This proposed filter is potentially applied in coarse wavelength division multiplexed (CWDM) systems.